The inner circle (Culper ring, ,, 2011)
A young archivist working in the National Archives and his childhood crush accidentally happen upon a priceless artifact--a 200-year-old dictionary that once belonged to George Washington--hidden inside a desk chair. Eager to discover why the President is hiding this important national treasure, the two soon find themselves entangled in a web of deception, conspiracy, and murder that will reveal the most well kept secret of the U.S. Presidency.

The fifth assassin (Culper Ring, ,, 2013)
Archivist Beecher White discovers a connection that may link the individuals responsible for the only four successful assassinations of American Presidents after discovering a modern-day killer who is recreating the assassins' crimes.

Ring of secrets (Culper Ring, 1,, 2013)
This exciting romantic spy novel from White combines fascinating cloak-and-dagger secrets with a tale of love and intrigue during the Revolutionary War.

Whispers from the shadows (Culper Ring, 2,, 2013)
Fleeing London to the safety of America, Gwenyth Fairchild seeks safety in the household of the Lane family in Maryland, but her safety is suspect when she discovers the Lanes are involved in espionage.

The President's shadow (Culper Ring, ,, 2015)
To most, it looks like Beecher White has an ordinary job. A young staffer with the National Archives in Washington, D.C., he's responsible for safekeeping the government's most important documents... and, sometimes, its most closely held secrets. But there are a powerful few who know his other role. Beecher is a member of the Culper Ring, a 200-year-old secret society founded by George Washington and charged with protecting the Presidency. Now the current occupant of the White House needs the Culper Ring's help. The alarming discovery of the buried arm has the President's team in a rightful panic. Who buried the arm? How did they get past White House security? And most important: What's the message hidden in the arm's closed fist? Indeed, the puzzle inside has a clear intended recipient, and it isn't the President. It's Beecher, himself. Beecher's investigation will take him back to one of our country's greatest secrets and point him toward the long, carefully hidden truth about the most shocking history of all: family history.